A Study on the Advanced Ophthalmic Training Program of Bangladesh (Journal of National Institute of Ophthalmology, 2022)
Aims: To describe the present status, strength, and weakness of the advanced ophthalmic training program in Bangladesh.Methods: A prospective study was carried out among the ophthalmologists those who had completed their long-term advanced ophthalmic training program (fellowship) in five tertiary eye hospitals of Bangladesh. The study period was from 01 January 2020 to 30 June 2020 including first three months data collection period. A semi-structured questionnaire was supplied to the study subjects. The analysis was made based on the answer from the study subjects.Results: The total responder was 46. The male responder was 58.7%, where the mean age of the study subjects was 33.05 years when they entered the training program. The Vitreo-retina fellows were the highest at 30.4%. Most of the fellows performed as the primary surgeon without supervision rather than surgery with supervision. Satisfied with the mentor was 91% while satisfied with hands-on work was 85% and satisfied with academic activities was 69.6%. About 21.7% of fellows did not involve any research work during the fellowship period. About 67.4% of fellows said that the central scientific session could be rearranged twice a week. However, 37% of fellows did not fulfill their logbook in the fellowship period.Conclusion: Most of trainees had got the opportunity to do hands on work but the supervision was inadequate. The research activities were not satisfactory in the advanced training period. There was not any unique training/fellowship curriculum among all institutes.J. Natl. Inst. Ophthalmol. 2022;5(1):32-38